Comparison of the analytical performance of the PATHFAST high sensitivity cardiac troponin I using fresh whole blood vs. fresh plasma samples - Gopi, Vinajak; Milles, Barbara Ruth; Spanuth, Eberhard; Müller-Hennessen, Matthias; Biener, Moritz; Stoyanov, Kiril M.; Frey, Norbert; Giannitsis, Evangelos (Clinical chemistry and laboratory medicine, 2021)
Objectives The PATHFAST hs-cTnI (high-sensitivity cardiac troponin) assay is the first point-of-care assay with a high-sensitivity designation that received FDA approval for diagnosis of myocardial infarction (MI). Testing from whole blood does not need centrifugation and therefore is faster and more convenient in the emergency room instead of plasma. However, there is sparse evidence whether point-of-care testing of Tn from whole blood is as reliable as from plasma samples. Methods We investigated the agreement between plasma and whole blood hs-cTnI by using the PATHFAST hs-cTnI assay. Hs-cTnT measured on Cobas 602 in the central laboratory and compared to a final diagnosis of NSTEMI using serial hs-cTnT served as reference. We assessed biases, limits of agreement (±1.96 SD) and coefficients of correlation, and tested the discriminatory ability of the baseline sample of plasma and whole blood hs-cTnI and plasma hs-cTnT to discriminate non-ST-segment elevation myocardial infarction (NSTEMI). Results A total of 224 paired fresh samples were collected simultaneously from 191 patients presenting with suspected acute coronary syndrome. There was an excellent correlation between plasma and whole blood hs-cTnI (r=0.99), and a very good inter-rater agreement (k=0.93) between elevated and normal plasma and whole blood results. Precision evaluation according to CLSI ep 15 revealed comparable coefficients of variation (CV) in whole blood and plasma. The discriminatory ability of baseline hs-cTnT, plasma and whole blood hs-cTnI was excellent (AUC 0.967, AUC 0.954 and AUC 0.953) without significant difference. Conclusions Whole blood can be used interchangeably with plasma for more convenient and less time and labor-consuming testing of hs-cTnI on the PATHFAST instrument.
Gesehen am 04.09.2021